1993
DOI: 10.1530/acta.0.1280274
|View full text |Cite
|
Sign up to set email alerts
|

The role of calcium ions in rat Leydig cell steroidogenesis induced by atrial natriuretic peptide

Abstract: Foresta C, Mioni R. The role of calcium ions in rat Leydig cell steroidogenesis induced by atrial natriuretic peptide. Acta Endocrinol 1993:128:274-80. ISSN 0001-5598 The aim of this study was to clarify whether calcium ions play a role in the mechanisms by which rat atriopeptin II exerts its stimulatory effects on rat Leydig cell steroidogenesis. The absence of calcium in the medium and the calcium channel-blocker drug, verapamil, both significantly inhibited testosterone production in rat atriopeptin Il-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Our results indicated that digitoxin have the inhibitory effect on the testicular function both in vivo and in vitro. This effect may partly result from the increased secretion of atrial natriuretic peptide (ANP) from atrial myocytes, and ANP can exert a potent direct inhibitory effect on testicular function [Mukhopadhyay et al, 1986;Foresta et al, 1993]. In addition, this study showed that digitoxin can act directly on the testicular interstitial cells to inhibit the secretion of testosterone (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Our results indicated that digitoxin have the inhibitory effect on the testicular function both in vivo and in vitro. This effect may partly result from the increased secretion of atrial natriuretic peptide (ANP) from atrial myocytes, and ANP can exert a potent direct inhibitory effect on testicular function [Mukhopadhyay et al, 1986;Foresta et al, 1993]. In addition, this study showed that digitoxin can act directly on the testicular interstitial cells to inhibit the secretion of testosterone (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…An early study suggested that long-term digoxin therapy may also depress LH secretion by the pituitary gland (Tappler & Katz, 1979), a phenomenon which would be expected to exacerbate the direct inhibitory actions of the drug on testicular testosterone secretion. Similarly, the digoxininduced blockade of testosterone synthesis in vivo may be reinforced by the concomitant fall of atrial natriuretic peptide (ANP), a peptide which stimulates testosterone secretion in vitro in a time and concentration-dependent manner (Mukhopadhyay et al, 1986;Foresta & Mioni, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies of the mechanism of action of erythropoietin addressed the possibility that cyclic nucleotides might serve as second messengers (18,19). It is well known that in rat Leydig cells both cAMP and cGMP are involved as second messengers in the steroidogenetic effect of agonists such as hCG and atrial natriuretic peptide (ANP) (21), [26][27][28][29]. However, the absence of any variation of cAMP and cGMP levels after rHuEPO treatment observed in this study suggests that in rat Leydig cells the affect of EPO, as well as of GnRH, does not involve adenylate or guanylate-cyclase systems.…”
Section: Discussionmentioning
confidence: 99%